Sociodemographic and clinical characteristics of type 2 diabetes mellitus patients with microangiopathies - Mendizábal, Teresa (2010)
Objective: To describe sociodemographic and clinical characteristics of diabetic patients with microangiopathies. Design: Descriptive, series of cases study. Setting: Hospital Nacional Daniel Alcides Carrion, Callao, Peru, a teaching hospital. Participants: Adult patients suffering of diabetes mellitus. Interventions: In 48 adult diabetes mellitus type 2 patients of both sexes, data was collected on age, sex, time of disease, glycemia and those possibly associated with absence of microangiopathies: education, socioeconomic level, minimal diabetic care (endocrinologist), standard diabetic care (endocrinologist and nutritionist), perception of family support, attending medical control, adherence to simple-sugar free diet and regular physical activity. Main outcome measures: Presentation of microangiopathies and other complications. Results: Average age was 55 and 52% patients suffered from microangiopathy. Non complicated patients had less age, duration of disease and family history of diabetes, higher education and socioeconomic level; better nutritional status and glycemia at the onset of diabetes and at time of interview. The only characteristic associated with absence of diabetic microangiopathies was standard diabetic care (endocrinologist and nutritionist) (p=0,013). Conclusions: Our findings agree with evidence of the positive effect of multidisciplinary intervention in diabetes on delaying or preventing microangiopathies.